Pervasive Computing Issues, Challenges and Applications (International Journal of Engineering and Computer Science, 2013)
This paper describes about the recent research topic pervasive computing which focus on the characteristics, architecture, issues and challenges. The pervasive architecture relates how the end-user interacts with the pervasive network using the middleware support. Finally it describes about the future focus for the pervasive computing through the real time applications